Vanadium-Substituted Wells-Dawson Heteropolyacid as Catalyst for Liquid Phase Oxidation of 1,4-Dihydropyridine Derivative - Sánchez, Laura Mabel (2013)
H7P2W17VO62.25H2O Wells-Dawson heteropolyacid was prepared, characterized and evaluated as catalyst in a 1,4-dihydropyridine oxidation reaction. The optimal conditions are the following: 1 mmol% of HWDV, a molar ratio 1,4-DHP:H2O2 (1:10) at reflux of acetonitrile. A conversion of 98.6 % is achieved in only 120 min of reaction.